Pengaruh Etos Kerja, Lingkungan Kerja, dan Kompensasi Terhadap Kinerja Guru MTs Al-Amanah Al-Gontory - Aisyah Almas Nurul Izzah; Singgih Aji Purnomo; Mohammad Muhtadi (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
This study aims to to determine the influence of Work Ethic, Work Environment, and Compensation simultaneously or each variable on the performance of MTs Al-Amanah Al-Gontory Teachers. This is a quantitative research, because this study uses a data collection method with questionnaires to retrieve the information needed by researchers. The data collection used in this study uses documentation and questionnaires using the Likert scale. Sampling uses the purposive sampling technique, which is a sampling technique with certain considerations where the respondents have been predetermined according to the number of minimum needs and respondent criteria. The research was carried out from March 2024 to May 2024 and used a sample of 63 respondents who were permanent teachers of the foundation who taught at MTs Al-Amanah Al-Gontory. The tests carried out in this study are instrument tests, classical assumption tests, multiple linear regression tests, and hypothesis tests. The results of the analysis showed that work ethic, work environment, and compensation had a positive and significant effect on teacher performance at a significance level of 5%. The F test also confirmed the significant influence of the three variables. The results of the determination coefficient (R²) prediction show that 58.3% of the variation in teacher performance can be explained by the three variables, while 41.7% is influenced by other factors outside the variables studied.